TIZ6938 Final Project and Internal Internship - Mohd Irwan, Dahnil Sikumbang (Faculty of Information Technology, 2007)
This business report is on Infinite Talent Sdn Bhd which was founded on February 2002. The company was established to provide an innovative Information Technology solutions. The report consist of information of company, resolution of business, corporate information, future plan, and audited report.